2011
DOI: 10.1038/cdd.2011.19
|View full text |Cite
|
Sign up to set email alerts
|

PIDD orchestrates translesion DNA synthesis in response to UV irradiation

Abstract: PIDD has been implicated in survival and apoptotic pathways in response to DNA damage, and a role for PIDD was recently identified in non-homologous end-joining (NHEJ) repair induced by c-irradiation. Here, we present an interaction of PIDD with PCNA, first identified in a proteomics screen. PCNA has essential functions in DNA replication and repair following UV irradiation. Translesion synthesis (TLS) is a process that prevents UV irradiation-induced replication blockage and is characterized by PCNA monoubiqu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
40
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(41 citation statements)
references
References 41 publications
1
40
0
Order By: Relevance
“…Tschopp identified a nuclear PIDD complex that contains PCNA (proliferating cell nuclear antigen), an important component of DNA repair machinery. 70 PCNA acts as a DNA sliding clamp that binds DNA polymerase and prevents its dissociation from the template DNA strand. The PIDD-PCNA complex is induced by UV stimulation and appears to facilitate the loading of PCNA onto template DNA.…”
Section: Remaining Questionsmentioning
confidence: 99%
“…Tschopp identified a nuclear PIDD complex that contains PCNA (proliferating cell nuclear antigen), an important component of DNA repair machinery. 70 PCNA acts as a DNA sliding clamp that binds DNA polymerase and prevents its dissociation from the template DNA strand. The PIDD-PCNA complex is induced by UV stimulation and appears to facilitate the loading of PCNA onto template DNA.…”
Section: Remaining Questionsmentioning
confidence: 99%
“…4 Large-scale immunoprecipitations with PIDD carried out in two different labs confirmed that most PIDD interactors appeared to be members from the DNA repair machinery and/or the cell cycle checkpoint machinery (C Du and A Villunger, personal communications). 41 Consistent with this, it is known that both PIDD and caspase-2 can be found in the nucleus (constitutively in the case of caspase-2 and upon DNA damage in the case of PIDD 30,37 ) and that caspase-2 is the only caspase identified so far with a nuclear localization signal in its prodomain. 42 Accumulating evidence from over the last few years point out that caspase-2 and PIDD might be implicated in pathways that act much earlier than DNA damage-induced apoptosis and are important for cell cycle control and DNA repair rather than cell death.…”
Section: Pidd and Nf-jb Activation: The Nemo Piddosomementioning
confidence: 60%
“…Of note, the relevance of some of these interactions remains to be formerly confirmed. The interaction between PIDD and DNA-PKc was confirmed by Logette et al 41 In addition, they detected almost all members of the proliferating cell nuclear antigen (PCNA)/ RFC/pold complex as PIDD-interacting partners, the PCNA PIDDosome (Table 1), and found a major role for PIDD in the monoubiquitination of PCNA upon DNA damage. PIDD overexpression or UV irradiation and concomitant PIDD induction triggers PCNA monoubiquitination upon release of p21.…”
Section: Pidd and Nf-jb Activation: The Nemo Piddosomementioning
confidence: 69%
See 2 more Smart Citations